Feeding ecology of fishes associated with artificial reefs in the northwest Gulf of Mexico - Dance, Kaylan M.; Rooker, Jay R.; Shipley, J. Brooke; Dance, Michael A.; Wells, R. J. David (PloS one, 2018)
The feeding ecology of two reef fishes associated with artificial reefs in the northwest Gulf of Mexico (GoM) was examined using gut contents and natural stable isotopes. Reefs were divided into three regions (east, central, west) across an east to west gradient of increasing reef complexity and salinity. Gray triggerfish (Balistes capriscus) primarily consumed reef-associated prey (xanthid crabs, bivalves, barnacles) and pelagic gastropods, while red snapper (Lutjanus campechanus) diets were mainly comprised of non-reef prey (stomatopods, fishes, portunid crabs). Natural stable isotopes of carbon (δ13C), nitrogen (δ15N), and sulfur (δ34S) were measured in consumer muscle tissue as well as potential primary producers. Gray triggerfish occupied a lower trophic position than red snapper, with lower δ13C and δ15N values across all size classes and regions, and generally higher δ34S values. Red snapper had a smaller range of stable isotope values and corrected standard ellipse areas across all size classes and regions, indicating a smaller isotopic niche. Contribution estimates of particulate organic matter (26 to 54%) and benthic microalgae (BMA, 47 to 74%) for both species were similar, with BMA contributions greater across all three size classes (juveniles, sub-adults, adults) of red snapper and all but the juvenile size class for gray triggerfish. Species gut contents and stable isotopes differed by region, with fishes consuming more crabs in the east region and more gastropods in the central and west regions. δ13C and δ15N values generally decreased from east to west, while δ34S increased across this gradient. Results highlight species-specific feeding differences associated with artificial reefs, where gray triggerfish may be more dependent on the reef structure for foraging opportunities. In addition, results offer further information on the integral role of BMA in primary production at nearshore artificial reefs.